Analisis Pemasangan Power System Stabilizer Pada Single Machine Infinite Bus Untuk Kondisi Variasi Beban - Muhammad Ruswandi Djalal; Makmur Saini; A.M Shiddiq Yunus (Jurnal JEETech, 2022)
Changes in the load on the electric power system suddenly cause dynamic disturbances. The disturbance causes the stability of the generator to be disturbed, because the generator does not respond to the disturbance quickly. This causes oscillations in the generator in the form of oscillations of frequency and rotor angle. One of the additional control equipment that can increase the stability of a generator is the Power System Stabilizer (PSS). With the PSS installation, the optimal frequency response and rotor angle of the SMIB system are obtained, indicated by the minimum system overshot response. The controller is able to provide stability so that overshoot oscillations can be suppressed, as well as faster settling time performance for the system to reach steady state conditions. To test the stability of the SMIB system, a case study of adding and subtracting loads is used, with the proposed control method using PSS.